Diagnosis dan Tatalaksana Rinolit Pada Pasien Lansia - Mizwar Mizwar; Effy Huriyati; Eti Yerizel (Pusat riset dan Inovasi Nasional, 2024)
Introduction: Rinolits are uncommon foreign bodies in the nose, which serve as a nidus for calcium salt deposition. Foreign bodies can be endogenous or exogenous in origin and can be asymptomatic for years before being discovered incidentally. If left untreated, stones can cause unilateral nasal obstruction, rhinorrhea, epistaxis, or in rare cases, progressive damage leading to septal/palatal perforation or oro-antral fistula. Surgical stone removal is an effective intervention with rare reports of complications. Case Report: A case of rinolit in a 72-year-old woman with complaints of left nasal congestion since 2 months ago with thick, smelly snot in the past 2 weeks is reported. History of foreign entry was denied. On examination of the sinistra nasal cavity, it was found that the nasal cavity was narrow, the inferior concha was edematous, there was a yellowish mass between the inferior concha and the septum, the media concha was difficult to assess, septal deviation was present, sekret was present, mucoid. The management given was extraction using forceps under local anesthesia. Conclusion: Rinolit is an uncommon clinical etiology which if undiagnosed can lead to complications; thus it is important to consider for any unilateral nasal symptoms of unclear origin.